(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the field of technology, the dimension of things has been smaller and smaller. The microwave frequency is fundamental part of various applications like Bluetooth, GSM and WLAN etc. These applications require antenna of varying size for better functioning. Nowadays technology becomes more advanced, the demand of such antenna has been increased which can operate at sufficient frequency range. To fulfill this requirement, the research suggests a design of single patch antenna using paper material as a substrate to enhance gain. The paper material is low cost, environment friendly, flexible material and organic also. This antenna is analyzed and simulated using Ansoft HFSS software (17.2). In this paper, single patch antenna and 2×1 patch array antenna are designed at 2.4GHz. The simulated peak gain of the single patch antenna is 2.05dB. The simulated peak gain of 2×1 patch antenna array is 2.70dB.